Design and Development of a Bilateral Therapeutic Hand Device for Stroke Rehabilitation. (13th December 2013) - Rahman, Akhlaquor; Al-Jumaily, Adel
The major cause of disability is stroke. It is the second highest cause of death after coronary heart disease in Australia. In this paper, a post stroke therapeutic device has been designed and developed for hand motor function rehabilitation that a stroke survivor can use for bilateral movement practice. A prototype of the device was fabricated that can fully flex and extend metacarpophalangeal (MCP), proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints of the fingers, and interphalangeal (IP), metacarpophalangeal (MCP) and trapeziometacarpal (IM) joints of the thumb of the left hand (impaired hand), based on movements of the right hand's (healthy hand) fingers. Out of 21 degrees of freedom (DOFs) of hand fingers, the prototype of the hand exoskeleton allowed fifteen degrees of freedom (DOFs), with three degrees of freedom (DOFs) for each finger and three degrees of freedom (DOFs) for the thumb. In addition, testing of the device on a healthy subject was conducted to validate the design requirements.